The Role of Village Heads in Sustainable Development Programs through the Formation of MSMEs (Micro, Small, and Medium Enterprises) (Case Study of Mentor Village, Sumberasih District, Probolinggo Regency) - Marwiyah, Siti; Y, Eko Yudianto; Zaini, Muhammad A’yun (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
The aim of this research is to find out the form of implementing Sustainable Development Goals (SDGs) through the role of the Village Head in the Sustainable Development Program through the formation of MSMEs and to find out what factors support or reduce the activities of implementing Sustainable Development Goals (SDGs through MSMEs) in Mentor Village, Sumberasih District, Probolinngo Regency. This research uses a descriptive qualitative research method that focuses on presenting data using role theory according to Sutarto, namely Role Conceptions, Role Expectations and Role Implementation. data collection techniques through direct observation, interviews with sources and documentation with several related parties. Researchers want to examine the implementation aspect of Sdgs in the formation of MSMEs (Micro, Small, and Medium Enterprises) in Mentor village